Hypercoagulability, endotheliopathy, and inflammation approximating 1 year after recovery: Assessing the long‐term outcomes in COVID‐19 patients. Issue 7 (28th April 2022) - Fan, Bingwen Eugene; Wong, Shiun Woei; Sum, Christina Lai Lin; Lim, Gek Hsiang; Leung, Bernard PuiLam; Tan, Chuen Wen; Ramanathan, Kollengode; Dalan, Rinkoo; Cheung, Christine; Lim, Xin Rong; Sadasiv, Mucheli Shravan; Lye, David Chien; et al.
Abstract: Sustained hypercoagulability and endotheliopathy are present in convalescent COVID‐19 patients for up to 4 months from recovery. The hemostatic, endothelial, and inflammatory profiles of 39 recovered COVID‐19 patients were evaluated up to 16 months after recovery from COVID‐19. These values were compared with a control group of healthy volunteers ( n  = 124). 39 patients (71.8% males, median age 43 years) were reviewed at a mean of 12.7 ± 3.6 months following recovery. One patient without cardiovascular risk factors had post COVID‐19 acute ischaemic limb. Elevated D‐dimer and Factor VIII levels above normal ranges were noted in 17.9% (7/39) and 48.7% (19/39) of patients respectively, with a higher median D‐dimer 0.34 FEU μg/mL (IQR 0.28, 0.46) ( p  < .001) and Factor VIII 150% (IQR 171, 203) ( p  = .004), versus controls. Thrombin generation (Thromboscreen) showed a higher median endogenous thrombin potential (ETP) of 1352 nM*min (IQR 1152, 1490) ( p  = .002) and a higher median peak height of 221.4 nM (IQR 170.2, 280.4) ( p  = 0.01) and delayed lag time 2.4 min (1.42–2.97) ( p  = 0.0002) versus controls. Raised vWF:Ag and ICAM‐1 levels were observed in 17.9% (7/39) and 7.7% (3/39) of patients respectively, with a higher median VWF:Ag 117% (IQR 86, 154) ( p  = 0.02) and ICAM‐1 54.1 ng/mL (IQR 43.8, 64.1) ( p  = .004) than controls. IL‐6 was noted to be raised in 35.9% (14/39) of patients, with a higher median IL‐6 of 1.5 pg/mL (IQR 0.6, 3.0) ( p  = 0.004) versus controls. Subgroup analysis stratifying patients by COVID‐19 severity and COVID‐19 vaccination preceding SARS‐CoV‐2 infection did not show statistically significant differences. Hypercoagulability, endothelial dysfunction, and inflammation are still detectable in some patients approximately 1 year after recovery from COVID‐19.